Business incubators as part of the development model of entrepreneurial ecosystems: Literature and business practice review - Milošev, Vladimir; Ćoćkalo, Dragan; Marić, Dubravko (Industrija, 2025)
Based on empirical evidence and examples of business incubators from different regions, this study provides an overview of the growing importance of business incubators in en-trepreneurial ecosystems as a structure for supporting innovation and economic development.  Drawing on groundbreaking research, this paper aims to clarify such dynamics while examining their effects on entrepreneurial efforts, proposing a sophisticated analysis of the impact of new technological and organisational trends on the role of business incubators. The study examines business incubators as support systems within entrepreneurial ecosystems, highlighting their evolution, important success factors, and emerging trends. A mixed methods approach was used, combining a systematic literature review with comparative analysis of case studies to identify key themes. This research draws on empirical evidence and case studies from different geographical contexts, integrating qualitative and quantitative data from academic literature and practical sources over the last decade. The study identifies strategic management, ecosystem integration, and adaptability to technological advances as important factors for incubation success. It reveals that sectoral and corporate incubators are playing an increasingly important role in shaping entrepreneurial ecosystems; it also advances understanding of the evolving role of business incubators and their integration into entrepreneurial ecosystems, offering insights for optimising their impact.
Keywords: business incubators, model, entrepreneurial infrastructure, technological innovation, entrepreneurial ecosystems